Patients’characteristics and Their Adherence to Insulin Therapy - Yunti Fitriani, - (Walter de Gruyter GmbH, 2020)
Background The prevalence of type 2 diabetes mellitus (DMT2) in Indonesia increased significantly from 6.9% (2013) to 8.5% (2018), putting Indonesia in top six countries in the world with maximum DMT2 patients. Patients with uncontrolled DMT2 are at risk for complications. As such, insulin is often administered to keep the levels under control. Unfortunately, poor adherence to insulin therapy is common, reflecting some factors that may affect the therapy. The aim of this study was to identify and analyze the characteristics of patients contributing to adherence to insulin therapy among DMT2 outpatients using the Health Belief Model (HBM) approach.